Acers in Nepal - Banerji, M. L.; Das, Sitesh (Indian Forester, 1971)
In this paper, the authors enumerate 13 species of Acers so far known to occur in Nepal. This observation is based on collections and published records. The character of the fruit has been studied in detail, laying particular emphasis on the angle of divergence of the wings which is in most cases of help in the identification of species. The authors have tried to clarify the confusion that exists in the older literature about the identity of four species, namely, A. caudatum; A. acuminatum; A. pectinatum and A. papilio, and have also given the correct identity of some species - A. sterculiaceum and A. cappadoicicum. The distribution of the species in Nepal is recorded.